Rise of the early Roman republic : reflections on becoming Roman - Dynneson, Thomas L., 1935- (Peter Lang, 2018)
An audaciously daring narrative, this text presents an overview of the early history of Rome, focusing the reader's attention to those distinctive and often hidden cultural features that contributed to create a unique ancient Roman mindset and civic outlook.